2019
DOI: 10.1039/c9ra02296a
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of benzonitrile using ionic liquid with multiple roles as the recycling agent

Abstract: ILs exhibited good co-solvent, catalytic, phase separation and recycling performance in the green synthesis of benzonitrile from benzaldehyde and (NH2OH)2·ILs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In recent years, the oximation-dehydration of aldehydes with hydroxylamine salts to synthesize nitriles has attracted the attention of researchers. [14][15][16][17] In our previous study, we reported the reaction of HMF with a hydroxylamine aqueous solution to obtain HMFO, with 98% conversion and 88% HMFC yield under the conditions of n(HMF) : n(NH 2 OH) = 1 : 1.5, H 2 O as the solvent, and 55 °C for 5 min. Based on this, the HMFC yield reached 100% when hydroxylamine zinc chloride salt (ZnCl 2 •2NH 2 OH) was used as the nitrogen source when the reaction was carried out at 100 °C for 20 min.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the oximation-dehydration of aldehydes with hydroxylamine salts to synthesize nitriles has attracted the attention of researchers. [14][15][16][17] In our previous study, we reported the reaction of HMF with a hydroxylamine aqueous solution to obtain HMFO, with 98% conversion and 88% HMFC yield under the conditions of n(HMF) : n(NH 2 OH) = 1 : 1.5, H 2 O as the solvent, and 55 °C for 5 min. Based on this, the HMFC yield reached 100% when hydroxylamine zinc chloride salt (ZnCl 2 •2NH 2 OH) was used as the nitrogen source when the reaction was carried out at 100 °C for 20 min.…”
Section: Introductionmentioning
confidence: 99%
“…This is a stable compound for pyrolysis, 4 an essential process in the synthesis of benzoic acid, benzylamine, benzamide, pesticides, and fatty amines, and dyes could be precursors for the synthesis of benzylamine, which can be used as a pharmaceutical intermediate. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Beside a wide distribution of natural products, benzonitrile as a simplest nitrogen-bearing aromatic molecules has been discovered recently in the interstellar medium. , Benzonitrile and its derivatives are comprising an important class of organic compounds in the chemical industry. This is a stable compound for pyrolysis, an essential process in the synthesis of benzoic acid, benzylamine, benzamide, pesticides, and fatty amines, and dyes could be precursors for the synthesis of benzylamine, which can be used as a pharmaceutical intermediate. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a stable compound to pyrolysis 4 an essential process in the synthesis of benzoic acid, benzylamine, benzamide, pesticides, fatty amines, dyes and could be precursors for the synthesis of benzylamine, which can be used as a pharmaceutical intermediate. 5,6 Also, benzonitrile is generally a good solvent for the synthesis of organic, anhydrous inorganic, and organometallic compounds and is generally similar in its behavior as a solvent to acetonitrile (CH3CN). 7 But, benzonitrile differs from acetonitrile in two interesting and significant ways: it has delocalized -electrons in the phenyl ring constantly interacting with the ̶ C≡N group, and it has a large phenyl group as compared to the methyl group creating a steric problem.…”
Section: Introductionmentioning
confidence: 99%